The chemicalome profiling of Zishen Yuzhen Pill in vivo and its promoting effect on osteogenic differentiation of MC3T3-E1 cells - Cheng, Juanjuan; Meng, Xinyue; Fang, Daozheng; Zhu, Yong; Liu, Zhihao; Li, Xinyue; Jie, Ke; Huang, Shiying; Li, Huilin; Zhang, Shangbin; Chen, Jihang; Chen, Jianping (Frontiers in Analytical Science, 2025)
Zishen Yuzhen Pill (ZYP) is a Chinese herbal product developed by Shenzhen TCM Hospital, which have been frequently used to treat osteoporosis (OP). This study aimed to determine the major chemical components of ZYP and its prototype compounds and metabolites in rat biological samples, as well as explore the potential effect of ZYP-containing serum in MC3T3-E1 cells. UPLC-Q/TOF-MS was used to identify the chemical components. Then, ZYP was orally administered to rat, and samples of plasma, urine, feces, bile, and tissue were collected to identify prototype compounds and metabolites. The viability of MC3T3-E1 cells was evaluated using the CCK-8 method after treatment with various concentrations (2%, 4%, and 8%) of ZYP-containing serum. Following treatment of MC3T3-E1 cells with ZYP-containing serum, the activity of alkaline phosphatase (ALP) and Alizarin red S (ARS) were measured, and the levels of Runx2, Opn, Opg and Osterix were quantified using the qPCR and Western blot analysis. And cells were collected for RNA-seq analysis. Results indicated that a total 152 compounds were identified in ZYP, including flavonoids, iridoid, lignans, triterpene saponins, etc. Furthermore, we detected a total of 70 prototype components and 99 metabolites distributed in different tissues. In addition, ZYP-containing serum observably promoted osteogenesis by increasing ALP and ARS activities, as well as up-regulating the expression of Runx2, Opn, Opg and Osterix in MC3T3-E1 cells. RNA-seq results indicated that the beneficial effects may be related to the upregulation of mitochondrial oxidative phosphorylation. This work provided further support for the traditional application of ZYP in the treatment of OP. And this study can promote the further pharmacokinetic and pharmacological evaluation of ZYP.